Plasmids for variable expression of proteins targeted to the mitochondrial matrix or intermembrane space. Issue 4 (1st October 2016) - Newman, Laura E.; Schiavon, Cara; Kahn, Richard A.
ABSTRACT: We describe the construction and uses of a series of plasmids for directing expression to varied levels of exogenous proteins targeted to the mitochondrial matrix or intermembrane space. We found that the level of protein expression achieved, the kinetics of expression and mitochondrial import, and half-life after import can each vary with the protein examined. These factors should be considered when directing localization of an exogenous protein to mitochondria for rescue, proteomics, or other approaches. We describe the construction of a collection of plasmids for varied expression of proteins targeted to the mitochondrial matrix or intermembrane space, using previously defined targeting sequences and strength CMV promoters. The limited size of these compartments makes them particularly vulnerable to artifacts from over-expression. We found that different proteins display different kinetics of expression and import that should be considered when analyzing results from this approach. Finally, this collection of plasmids has been deposited in the Addgene plasmid repository to facilitate the ready access and use of these tools.